Portrait of the San Jose Police Department motorcyle unit - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the San Jose Police Department motorcycle unit, standing beside their motorcycles in front of the San Jose Civic Auditorium .